Improving lecturer fitness through physical activity: A study with rhythmic gymnastics and regular walking - Kafrawi, Fatkur Rohman; Purnomo, Mochamad; Ashadi, Kunjung; Jimenez, Jose Vicente Garcia; Rusdiawan, Afif (Journal Sport Area, 2025)
Background: Maintaining excellent physical fitness not only enhances mental well-being but also fosters teachers' ingenuity and inventiveness in devising effective teaching strategies. A fit body will be able to increase concentration, which means a teacher can deliver learning material better and achieve goals. Consequently, pupils become more engaged and comprehend the instructional material more easily. Research Objectives: This study aims to determine the effect of rhythmic gymnastics and walking more than 7,500 steps per day for 8 weeks on fitness and BMI. Methods: The employed research method was quantitative research using a causal-associative approach. This study utilised 43 participants who met the following criteria: they were between the ages of 35 and 55, actively engaged as lecturers in the teacher professional education program (PPG) at Universitas Negeri Surabaya, and willing to participate in the study for a duration of 60 days, during which they would receive the given intervention. The intervention given was in the form of Indonesian teacher gymnastics with a composition of 2 minutes of warm-up, 11 minutes of core, and 2 minutes of cool-down. In addition to gymnastics, the intervention involved walking at least 7,500–8,000 steps per day, every day, for a duration of 8 weeks (60 days). For sample step control, samples are required to send a report of their daily steps that have been recorded through the Pedometer-SStep Counter App. Data analysis used paired t-tests and SPSS 23 software to assess the intervention's impact on body mass index and fitness. Findings and Results: The results showed that combined rhythmic gymnastics training (Indonesian Teachers Gymnastics) and walking more than 7,500 for 8 weeks can increase VO2 max (pre 28.68 11.37; post 32.08 13.26; p = 0.000), but did not significantly affect changes in BMI (pre 25.51 4.88; post 25.43 4.02; p = 0.760). Conclusion: Rhythmic gymnastics training and daily 7,500 steps of walking for 8 weeks can improve cardiorespiratory fitness in middle-aged professionals but may not alter BMI. This simple, accessible workplace health program can enhance cardiovascular fitness.